Beyond the republican revival : non-domination, positive liberty and sortition - Ghosh, Eric (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This is the first book-length treatment of both the non-positive and the positive-liberty strands of the republican revival in political and constitutional theory. The republican revival, pursued especially over the last few decades, has presented republicanism as an exciting alternative to the dominant tradition of liberalism. The book provides a sharply different interpretation of liberty from that found in the republican revival. The book argues that this different interpretation is not only historically more faithful to some prominent writers identified with the republican tradition, but is also normatively more attractive. The normative advantages are revealed through discussing some central concerns relating to democracy and constitutionalism, including the justification for democracy and the interpretation of constitutional rights. The book also looks beyond republican liberty by drawing on the republican device of sortition (selection by lot). The book proposes the use of large juries to decide bill-of-rights matters. This novel proposal indicates how democracy might be reconciled with constitutional review based on a bill of rights. Republicanism is not pitted against liberalism: the favoured values and institutions fit with liberal commitments"--
Introduction -- Pettit's narrative of the eclipse of republican liberty -- Skinner's republican and liberal liberty -- The challenge of liberty as non-interference -- Vindicating liberty as non-domination -- Positive-liberty dimensions in the republican revival -- Michelman's republicanism -- A citizens' court : foundations -- A citizens' court : the proposal -- Conclusion.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Republicanism; Liberty; Constitutional & administrative law; Electronic books